Does Pneumatosis Intestinalis after Etoposide Chemotherapy always have a Benign Course? - DENİZBAŞI ALTINOK, ARZU; AKOĞLU, HALDUN (AVES, 2016)
Introduction: Pneumatosis intestinalis (PI) was reported in hematological malignancies in immunosuppressive patients who were being administered chemotherapy and steroids. However, PI generally has a benign course and is usually conservatively treated in these patients. In this case, we presented a patient who underwent chemotherapy because of testis neoplasm and was admitted to the hospital with abdominal pain, vomiting, and high blood glucose levels, and the patient died because of PI and mesenteric ischemia. Case Report: A 38-year-old man who had type 1 diabetes mellitus and had undergone chemotherapy (bleomycin, etoposide, cisplatin, and corticosteroids) for testis neoplasm presented to the emergency room with abdominal pain. His blood glucose level was 547 mg/dL. In blood gases analyses, pH=7.30, cHCO3=15, and lactate=3.2 and ketone was positive in urine analyses. He had no specific finding on physical abdominal examination. He had undergone diabetic ketoacidosis treatment. Because his abdominal pain persisted, abdominal tomography was performed and diffuse intestinal wall necrosis and gas was observed in the portal system. He was operated and died in the intensive care unit after surgery. Conclusion: In the emergency department, it is important to be aware of mesenteric ischemia (MI), particularly in patients who undergone chemotherapy and who were admitted to the hospital with abdominal pain. Quick and further testing for MI is necessary.
Keywords: Pneumatosis intestinalis; mesenteric ischemia; abdominal pain; etoposide